The Development of Victoria as a Retirement Centre - Forward, Charles (Urban History Review / Revue d'histoire urbaine, 1984)
The significance of Victoria as a retirement location relative to other cities in Canada is the major focus of the article. Census data on the proportion of elderly and middle aged population in Canadian cities is investigated, as well as data on the migration of the elderly. Victoria is compared with other Canadian cities to determine when it became a significant destination for retirement and the degree of distinctiveness it achieved as a retirement centre since that time.